(untitled) (Journal of the Pakistan Medical Association, 2020)
Objective: To assess the frequency of maxillary ectopic canine both buccally and palatally displaced with incisor root resorption and dental agenesis. Methods: The cross-sectional study was conducted from April 8 to June 29, 2019, at the Department of Orthodontics, Dr. Ishrat Ul Ebad Khan Institute Of Oral Health Sciences, and Dow Dental College, Dow University Of Health Sciences, Karachi, and comprised orthodontic patients diagnosed with maxillary ectopic canine eruption. Root resorption and agenesis were diagnosed on panoramic films. Root resorption was further confirmed by periapical radiographs. Data was analysed using SPSS 21. Results: Of the 98 subjects, 86(87.8%) had buccally displaced canines of which 38(44.2%) were associated with root resorption, while 12(12.2%) patients had palatally displaced canines of which 10(83.3%) had root resorption (p=0.011). Overall, 30(30.6%) lateral incisors were resorbed, 7(7.1%) both central and lateral incisors, 5(5.1%) premolars, and 6(6.1%) both lateral incisors and premolars were resorbed. Agenesis was detected in 10 (10.2%) subjects (p=0.62). Conclusion: There was found to be no association of maxillary ectopic canines with incisor root resorption and dental agenesis. Key Words: Root resorption, Agenesis, Ectopic canine, Buccally displaced canine, Palatally displaced canine.